Relationships between self-efficacy, health belief, and self-care among type 2 diabetes mellitus - Cahyani, Isnaini Putri; Fatimah, Fatma Siti; Rosyida, Ratna Wirawati (Journal of Community Empowerment for Health, 2024)
Introduction: Diabetes mellitus (DM) patients need to be empowered to manage their conditions. Some factors that affected the empowerment of diabetes mellitus patients were self-efficacy, health beliefs, and self-care. Self-efficacy positively correlates with health belief and self-care among patients with type 2 DM. However, such evidence is still limited in the Health Care Centers, especially in Yogyakarta. This research aimed to identify self-efficacy and the relationship between health belief and self-care among Type 2 DM patients. Methods: This is a correlative analytical of quantitative research using the cross-sectional approach. Purposive sampling was used to collect the samples, which were 83 patients who belonged to the inclusion criteria. This research was conducted in the Primary Health Center in Bantul Yogyakarta between April and May. The statistical tests used the Spearman rank correlation test due to the abnormal distribution. Results: The mean of self-efficacy, health belief, and self-care were 84.9±9.3; 105,1±7,2; 67,8±7,7, respectively. There was a significant relationship between self-efficacy and health belief at the value of p<0.000, and there was a relationship between self-efficacy and self-care at the value of p<0.000. Conclusion: Positive correlations were achieved between self-efficacy and health belief and between self-efficacy and self-care in diabetes mellitus patients.